Dynamic landscape of tandem 3′ UTRs during zebrafish development - Li, Yuxin; Sun, Yu; Fu, Yonggui; Li, Mengzhen; Huang, Guangrui; Zhang, Chenxu; Liang, Jiahui; Huang, Shengfeng; Shen, Gaoyang; Yuan, Shaochun; Chen, Liangfu; Chen, Shangwu; et al. (Genome Research, 2012)
Tandem 3′ untranslated regions (UTRs), produced by alternative polyadenylation (APA) in the terminal exon of a gene, could have critical roles in regulating gene networks. Here we profiled tandem poly(A) events on a genome-wide scale during the embryonic development of zebrafish (Danio rerio) using a recently developed SAPAS method. We showed that 43% of the expressed protein-coding genes have tandem 3′ UTRs. The average 3′ UTR length follows a V-shaped dynamic pattern during early embryogenesis, in which the 3′ UTRs are first shortened at zygotic genome activation, and then quickly lengthened during gastrulation. Over 4000 genes are found to switch tandem APA sites, and the distinct functional roles of these genes are indicated by Gene Ontology analysis. Three families of cis-elements, including miR-430 seed, U-rich element, and canonical poly(A) signal, are enriched in 3′ UTR-shortened/lengthened genes in a stage-specific manner, suggesting temporal regulation coordinated by APA and trans-acting factors. Our results highlight the regulatory role of tandem 3′ UTR control in early embryogenesis and suggest that APA may represent a new epigenetic paradigm of physiological regulations.
10.1101/gr.128488.111